2002
DOI: 10.1016/s0014-5793(02)02807-7
|View full text |Cite
|
Sign up to set email alerts
|

Short‐time non‐enzymatic nitric oxide synthesis from L‐arginine and hydrogen peroxide induced by shock waves treatment

Abstract: The evidence that nitric oxide (NO) production is possible by a non-enzymatic pathway has already been shown under restrictive experimental conditions. Here we show that NO can non-enzymatically be formed with short-time kinetics (min), by 'bombing' with shock waves a solution containing 1 mM hydrogen peroxide and 10 mM L-arginine. This procedure is widening its medical application with surprisingly positive effects in tissue regeneration and our finding could be one of the first steps for the understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(77 citation statements)
references
References 20 publications
1
73
0
3
Order By: Relevance
“…Because the physical forces generated by cavitation are highly localized, SW could induce localized stress and subsequent shear stress on cell surface membranes (Fisher et al 2001). Several biochemical effects of SW were reported including hyperpolarization, Ras activation, non-enzymatic NO synthesis, and induction of stress fibers and intercellular gaps (Seidl et al 1994;Wang et al 2001;Gotte et al 2002). Also, SW treatment is reported to affect the expression of several chemokines and matrix metalloproteinases and therefore bring anti-inflamatory effects Mariotto et al 2005;Stojadinovic et al 2008;Mariotto et al 2009) in addition to up-regulation of VEGF and its receptor Flt-1 (Nishida et al 2004), implying that the multiple angiogenic pathways are involved in the beneficial effects of the SW therapy.…”
Section: Mechanisms For Sw-induced Neovascularizationmentioning
confidence: 99%
“…Because the physical forces generated by cavitation are highly localized, SW could induce localized stress and subsequent shear stress on cell surface membranes (Fisher et al 2001). Several biochemical effects of SW were reported including hyperpolarization, Ras activation, non-enzymatic NO synthesis, and induction of stress fibers and intercellular gaps (Seidl et al 1994;Wang et al 2001;Gotte et al 2002). Also, SW treatment is reported to affect the expression of several chemokines and matrix metalloproteinases and therefore bring anti-inflamatory effects Mariotto et al 2005;Stojadinovic et al 2008;Mariotto et al 2009) in addition to up-regulation of VEGF and its receptor Flt-1 (Nishida et al 2004), implying that the multiple angiogenic pathways are involved in the beneficial effects of the SW therapy.…”
Section: Mechanisms For Sw-induced Neovascularizationmentioning
confidence: 99%
“…Results are expressed as means ± S.E.M. dated; however, it has been demonstrated that SW can cause non-enzymatic nitric oxide (NO) synthesis from L-arginine and hydrogen peroxide (Gotte et al 2002), and that SW induces neovascularization at tendon (Rompe et al 1995;Wang et al 2003) and up-regulates the expression of eNOS, VEGF, and proliferating cell antigen (PCNA) (Wang et al 2003). We have previously confi rmed that low-energy SW up-regulates VEGF and its receptor, Flt-2, in endothelial cells in vitro and VEGF in the ischemic porcine myocardium in vivo (Nishida et al 2004).…”
Section: Mechanism Of the Sw Therapy-induced Angiogenesismentioning
confidence: 99%
“…Total cellular RNA was purified as described above and reverse transcribed into cDNA, using MMLV reverse transcriptase and oligo dT (12)(13)(14)(15)(16)(17)(18) as primers. cDNA was amplified for the iNOS gene (450 bp) or TNF-a gene (200 bp) using specific primers (iNOS forward: 5 0 -TCCTTGCATCCTCATCGGGCC-3 0 , iNOS reverse: 5 0 -TCGTGA-TAGCGCTTCTGGCTCT-3 0 ; TNFa forward: GAGCTGAGAGA-TAACCAGCTGGTG-3 0 , TNFa reverse 5 0 -CAGATAGATGGGC-TCATACCAGGG-3 0 ).…”
Section: Rt-pcrmentioning
confidence: 99%
“…In this respect, we have reported that NO is produced non-enzymatically by the treatment of a L L-arginine/hydrogen peroxide mixture with ESW, although this NO production requires higher energy potencies (0.89 mJ/mm 2 ) than those employed clinically [12].…”
Section: Introductionmentioning
confidence: 99%